Cloud Computing in Education - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal on Human-Computing Studies, 2023)
A cloud platform makes it easier for students and teachers to access educational resources. Lesson plans, coursework, and assignments can be uploaded, updated, and accessed anytime by students. It is easy for educators to monitor coursework and access students’ progress without having to meet face-to-face. A teacher can work from anywhere, connect their students to multiple programs and applications, and save all their lesson plans and assignments to the cloud. This paper provides an introduction on cloud computing for education.